Prevalência de sobrepeso e obesidade em adolecentes escolares do município de Fortaleza - Campos, Lício de Albuquerque (2004)
The aim of this study was to determine the prevalence of the overweight and obesity in adolescents from public and private schools in the city of Fortaleza, Brazil. The overweight and obesity prevalence was analyzed considering gender and age, as well as the family’s socioeconomic background. A population-based cross-sectional study was conducted between March and May of 2003, including a sample of 1,158 adolescents (10 to 19 years old) enrolled in elementary education (between the fifth and eight grades) and in high school. The variables included in this study were: gender, age group (early adolescence- 10 to14 years old and late adolescence-15 to 19 years old), type of school (public or private), socioeconomic level, and anthropometric measures. The Body Mass Index (BMI) was used in the nutritional assessment. Overweight was defined as the BMI equal or above to the 85 percentile and below to the 95 percentile while obesity was defined as BMI equal or above to the 95 percentile. The reference of the anthropometric measures was based on the tables provided by Must et al. (1991). The economic classification of Brazil (IBOPE) was used to determine the socioeconomic level. The overall prevalence of overweight/obesity was 19.5%; the proportion in private schools was higher than in public schools (23.9 e 18.0%, respectively). Regarding gender, the overweight incidence was similar in both types of schools; however, its prevalence among males was higher in private schools while no difference among males and females was found in public schools. Overweight/obesity prevalence among adolescents aged 10 to 14 years old was higher than among adolescents aged 15 to 19 years old. The highest rates were found in the highest SES stratum, being males and adolescents aged 10 to14 years old responsible for this difference. It was concluded that the prevalence of overweight/obesity among adolescents in the city of Fortaleza is considerably elevated, being higher in private schools, in the early adolescence, and in the highest SES level. No difference was found in this rate among males and females.